2006
DOI: 10.1109/tvcg.2006.106
|View full text |Cite
|
Sign up to set email alerts
|

TreePlus: Interactive Exploration of Networks with Enhanced Tree Layouts

Abstract: Abstract-Despite extensive research, it is still difficult to produce effective interactive layouts for large graphs. Dense layout and occlusion make food webs, ontologies, and social networks difficult to understand and interact with. We propose a new interactive Visual Analytics component called TreePlus that is based on a tree-style layout. TreePlus reveals the missing graph structure with visualization and interaction while maintaining good readability. To support exploration of the local structure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The works most closely related to ours are TreePlus by Lee et al [32] and the application-specific variant of TreePlus, GOTreePlus [30]. TreePlus introduces the "plant a seed and watch it grow" principle.…”
Section: Tree-based Graph Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The works most closely related to ours are TreePlus by Lee et al [32] and the application-specific variant of TreePlus, GOTreePlus [30]. TreePlus introduces the "plant a seed and watch it grow" principle.…”
Section: Tree-based Graph Visualizationmentioning
confidence: 99%
“…A common strategy to explore large graphs is a bottom-up approach, where the analysis begins with a search or a query, and then more context is added as needed [49,50]. Flavors of this approach range from explicitly revealing neighborhoods of nodes [18,32], to querying for paths or connectivity in a network [27,40], to querying based on a degree-of-interest function [49], to associative browsing and complex queries [25,46]. All these examples are designed to return or expand a single subgraph, in contrast to techniques such as VIGOR [42] that are used to analyze (typically structural) queries that return many different subgraphs.…”
Section: Query-based Visualization Of Large Graphsmentioning
confidence: 99%
“…In bottom-up approaches, the exploration starts with a small subset of a graph that can then be expanded. For example, in Treeplus [LPP* 06a] a graph can be continuously expanded in a flexible tree layout, starting from a seed node. Ham and Perer [vHP09], Abello et al [AHSS13], and Luger et al [LSG* 15] use more sophisticated methods to select and expand graph subsets based on degree of interest functions.…”
Section: Related Workmentioning
confidence: 99%
“…Previous research showed that querying tools greatly benefit from having intuitive visual user interfaces, through which the user can more naturally specify queries and understand the resulting matches [5, 8, 12]. …”
Section: Our Completed Work and Related Workmentioning
confidence: 99%
“…This points to the need for intuitive visual user interfaces that helps the user to both specify their queries and visualize the matches, as such interfaces are easier to use and can help the user understand the results [5, 8, 12]. …”
Section: Introductionmentioning
confidence: 99%